SYSTEM AND METHOD FOR FIELD MAP ESTIMATION (2013)
max0A system and method for determining a magnetic field map when using a magnetic resonance imaging (MRI) system to acquire images from a region of interest (ROI) of a subject. The method includes selecting a pulse sequence to elicit a plurality of echoes from the subject as medical imaging data from the subject. The method also includes optimizing an echo time for a dynamic range of interest during the pulse sequence (SB), a minimum signal-to-noise ratio (SNR) in the medical imaging data, and minimum T2* value in the ROI. The method further includes generating a magnetic field map estimation using the optimized echo times.